2014
DOI: 10.1111/epi.12789
|View full text |Cite
|
Sign up to set email alerts
|

Premature mortality in poor health and low income adults with epilepsy

Abstract: SUMMARY Objective To examine mortality and causes of death (COD) in socioeconomically disadvantaged persons with epilepsy (PWE) in the US. Methods We performed a retrospective open cohort analysis using Ohio Medicaid claims data between 1992 and 2008 to assess mortality and COD in 68,785 adult Medicaid beneficiaries with epilepsy. Case fatality (CF), mortality rates (MRs), standardized mortality ratios (SMRs), and years of potential life lost (YPLL) were calculated. The SMRs were estimated to compare risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 43 publications
(107 reference statements)
1
47
3
Order By: Relevance
“…66 Several Western studies have reported lower SMRs than in Asia. In the USA, the SMR of socioeconomically deprived patients with epilepsy was 1.8, 67 and two European studies found overall SMRs of 1.7-2.2 compared with the general population of the same geographic area. 56,57 Seizure-related causes of death, especially nonvehicle accidents, 63 played a greater role in the higher mortality of Asian people with epilepsy than in Western studies, indicating the importance of seizure control to prevent premature death.…”
Section: Mortalitymentioning
confidence: 98%
See 3 more Smart Citations
“…66 Several Western studies have reported lower SMRs than in Asia. In the USA, the SMR of socioeconomically deprived patients with epilepsy was 1.8, 67 and two European studies found overall SMRs of 1.7-2.2 compared with the general population of the same geographic area. 56,57 Seizure-related causes of death, especially nonvehicle accidents, 63 played a greater role in the higher mortality of Asian people with epilepsy than in Western studies, indicating the importance of seizure control to prevent premature death.…”
Section: Mortalitymentioning
confidence: 98%
“…A recent Hong Kong study found a standardized mortality ratio (SMR) of 5.09 among newly diagnosed patients with epilepsy . The SMR was higher among patients with baseline physical and/or psychiatric comorbidity and highest for those with both physical and psychiatric comorbidities (Table ) . Two studies from Taiwan found SMRs for patients with epilepsy of 2.5 and 3.47, with the age‐specific SMRs being highest for boys and young women .…”
Section: Burden Of Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…Among United States young adults with epilepsy and low socioeconomic status, deaths occur 17 years prematurely. 6 …”
Section: Introductionmentioning
confidence: 99%